GAMBARAN KARAKTERISTIK PASIEN KOMPLIKASI DIABETES DI RUMAH SAKIT KRISTEN NGESTI WALUYO PARAKAN - Miranti Puspasari; Ari Udiyono; Sri Yuliawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Diabetes Mellitus (DM) is one of the degenerative diseases that occur because the amount of insulin in the body is not balanced that can cause complications and can not be cured but can be prevented by the existence of good management or self-management of patients. The purpose of this study is to describe the characteristics of patients with complications of type 2 diabetes mellitus. This research is an observational analytical study with cross sectional approach. The instrument used in this study is a questionnaire. The sample selection in this research use consecutive sampling technique. The results showed the characteristics of diabetes mellitus in the age group> 45 years (86.7%), female gender (81.7%), educational background in elementary school group (53.3%), work status (61.7%) , old status of diabetes mellitus type 2 <4 years and ≥ 4 (50%), lack of knowledge (58,3%), negative perception (58,3%), and self-management less (56,7%). To the Christian Hospital, Ngesti Waluyo Parakan is expected to provide information and education considering the nutritional factors, diabetes mellitus, symptoms of diabetes mellitus.